New insights into the roles of CHOP-induced apoptosis in ER stress - Li, Yiming; Guo, Yunshan; Tang, Juan; Jiang, Jianli; Chen, Zhinan (Acta biochimica et biophysica Sinica, 2014)
Endoplasmic reticulum stress （ER stress） is triggered due to a loss of homeostasis in the ER, resulting in accu- mulation of misfoided proteins in the ER lumen. ER stress activates a series of adaptive mechanisms known as the unfolded protein response. Perturbation of the ER is a powerful inducer of the transcription factor C/EBP hom- ologous protein （CHOP）. Although it has been proved that excessive or adverse stress to the ER triggers apoptosis, the specific mechanisms underlying these processes induced by CHOP remain unclear. By now, CHOP-induced apoptosis in ER stress has been implicated in numerous human dis- eases, such as neurodegenerative diseases, diabetes, ische- mic diseases, tumor, and so on. In this review, we summarized the current understanding of the roles of CHOP in the development of several diseases from the laboratory to the clinic.